PENGARUH GOOD CORPORATE GOVERNANCE, CAPITAL INTENSITY RATIO, LEVERAGE, DAN FINANCIAL DISTRESS TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN TAMBANG YANG TERDAFTAR DI BEI TAHUN 2013-2017 - Ruth Rogate Octaviani; Sofie Sofie (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
This study is aimed to examine the effect of good corporate governance, capital intensity ratio, leverage and financial distress on tax aggressiveness. Using samples from mining sectors listed on the Indonesia Stock Exchange in period 2013-2017, the data will be examined with random effect approach method. The results of this study good corporate governance of the managerial ownership and institutional ownership not effect on tax aggressiveness, meanwhile independent commissioners affect positive significantly on tax aggressiveness. While from capital intensity ratio which affect positive significantly on tax aggressiveness. In addition, leverage affect negative significantly on tax aggressiveness and financial distress variable, does not effect on tax aggressivess.